FACTORS AFFECTING THE YOUNG MUSLIM GENERATION IN PURCHASING IMPORTED PRODUCTS - Hidayat, Ali Akbar; Moh. Huzaini; Ihsan Ro'is; Septiawan, Adi; Suhardi, Rizal M. (Elastisitas : Jurnal Ekonomi Pembangunan, 2023)
The decision to purchase a product is based on various factors that influence it. This research aims to analyses the factors influencing the decision to buy imported products by Generation Z Muslims in West Nusa Tenggara. This research is quantitative research with an associative approach. Sample collection in the study used non-probability sampling with a purposive sampling approach. This research uses the smart-PLS analysis tool. The results of the research show that the halal label has a negative but insignificant effect on the decision to purchase imported products by Muslim generation Z, brand image has a positive and significant effect on the decision to buy imported products by Muslim generation Z, and religiosity has a positive but insignificant effect on the decision to buy imported products by Muslim generation Z. Meanwhile, the policy implication that can be implemented is that providers of imported products must pay attention to the brand image of these foods which can attract Muslim Generation Z consumers in West Nusa Tenggara.